2018
DOI: 10.1016/j.rpor.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a protein corona influences the biological identity of nanomaterials

Abstract: The development and testing of nanomaterials is an area of interest due to promising diagnostic and therapeutic applications in the treatment of diseases like cancer or cardiovascular disease. While extensive studies of the physicochemical properties of nanoparticles (NPs) are available, the investigation of the protein corona (PC) that is formed on NPs in biofluids is a relatively new area of research. The fact that few NPs are in clinical use indicates that the biological identity of NPs, which is in large p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 74 publications
4
58
0
Order By: Relevance
“…[ 20,55 ] Additionally, NP permeability in the presence of culture medium can be affected by the formation of a protein corona around NPs. [ 56,57 ] On the other hand, PU NPs were functionalized using a PEGylated Tf: the PEG segment functioned as a spacer, providing Tf flexibility and exposure, [ 58 ] and as an anti‐fouling agent, reducing nonspecific protein adsorption, [ 59 ] and preserving Tf biological function. Hence, PU‐Tf NPs presented Tf more effectively to TfRs on iPSC‐ECs, possibly resulting in improved transcytosis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20,55 ] Additionally, NP permeability in the presence of culture medium can be affected by the formation of a protein corona around NPs. [ 56,57 ] On the other hand, PU NPs were functionalized using a PEGylated Tf: the PEG segment functioned as a spacer, providing Tf flexibility and exposure, [ 58 ] and as an anti‐fouling agent, reducing nonspecific protein adsorption, [ 59 ] and preserving Tf biological function. Hence, PU‐Tf NPs presented Tf more effectively to TfRs on iPSC‐ECs, possibly resulting in improved transcytosis.…”
Section: Discussionmentioning
confidence: 99%
“…From the results, it can be safely concluded that the cellular response of Y 2 O 3 NPs is actually the response of complete-media-component (that include serum proteins as well media ingredients) coated-Y 2 O 3 NPs rather than only serum protein coated NPs. Thus, living systems mostly interact with the surface modified NPs rather than with bare NPs only when the NPs are surface reactive [32,33]. Bio-molecular corona formed on surface reactive NPs can provide stealth effect during NP uptake by immune cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…After systemic administration, NPs are exposed to the complex environment of blood where they interact with multiple proteins (Nierenberg, Khaled, & Flores, 2018;Tenzer et al, 2013). After systemic administration, NPs are exposed to the complex environment of blood where they interact with multiple proteins (Nierenberg, Khaled, & Flores, 2018;Tenzer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moving forward, future studies will need to be performed to assess the efficacy and safety of this technology in vivo, and to evaluate its use as a platform for dual miRNA and drug delivery. After systemic administration, NPs are exposed to the complex environment of blood where they interact with multiple proteins (Nierenberg, Khaled, & Flores, 2018;Tenzer et al, 2013). These proteins can coat the NPs, resulting in NP sequestration and clearance via the mononuclear phagocytic systems (MPS), reducing their circulation half-life (Albanese, Tang, & Chan, 2012;Lazarovits, Chen, Sykes, & Chan, 2015).…”
Section: Discussionmentioning
confidence: 99%